2015
DOI: 10.1111/1462-2920.12855
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genotype and environment drive the metabolic phenotype within Escherichia coli isolates

Abstract: To gain insights into the adaptation of the Escherichia coli species to different environments, we monitored protein abundances using quantitative proteomics and measurements of enzymatic activities of central metabolism in a set of five representative strains grown in four contrasted culture media including human urine. Two hundred and thirty seven proteins representative of the genome-scale metabolic network were identified and classified into pathway categories. We found that nutrient resources shape the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…In another long‐term continuous culture of E. coli, where glucose was provided as sole carbon source, two subpopulations evolved: one, which utilized glucose and produced acetate as a metabolic by‐product and a second subpopulation, which specialized to utilize the exogenously available acetate . Consequently, the utilization of different carbon sources can cause significant differences in the distribution of metabolic fluxes and, as shown in this study, different biosynthetic costs. Interestingly, the amino acid biosynthetic cost differences between the two specialized subpopulations in the two above‐mentioned examples are highly reciprocal, because glucose is a glycolytic carbon source, whereas citrate or acetate, respectively, are gluconeogenic substrates (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…In another long‐term continuous culture of E. coli, where glucose was provided as sole carbon source, two subpopulations evolved: one, which utilized glucose and produced acetate as a metabolic by‐product and a second subpopulation, which specialized to utilize the exogenously available acetate . Consequently, the utilization of different carbon sources can cause significant differences in the distribution of metabolic fluxes and, as shown in this study, different biosynthetic costs. Interestingly, the amino acid biosynthetic cost differences between the two specialized subpopulations in the two above‐mentioned examples are highly reciprocal, because glucose is a glycolytic carbon source, whereas citrate or acetate, respectively, are gluconeogenic substrates (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Lactose allows the growth of the vast majority of E. coli strains [31]. It has been shown that the lag time and generation time of E. coli strains, which depend on metabolic efficiency and are crucial for gut colonization and persistence [32,33], are influenced by the type and abundance of available nutrients in the habitat [34]. Other components of milk replacers may have also influenced the E. coli population dynamics, such as vitamin D, for which the absence of the vitamin D receptor in the intestinal epithelium of mice has been associated with increased E. coli loads [35].…”
Section: Discussionmentioning
confidence: 99%
“…6B). It has been shown that the point, at which a carbon source enters the central metabolic network, strongly affects the distribution of metabolic uxes 169,170 and, in this way, also the production costs of individual amino acids. 164 Hence, a consequence of diverse carbon source preferences is that one species of the bacterial community can have a comparative advantage in the biosynthetic cost efficiency of a specic set of metabolites over another species, which in turn has a comparative advantage in the production of another set of metabolites ( Fig.…”
Section: Metabolic Factorsmentioning
confidence: 99%